Analyze Farmers' Attitudes, Skills, and SDG Achievements through the Production of Organic Fertilizer from Corn Cobs - Sri Adelila Sari; Prastowo, Puji; Muslim, Muslim; Kabeakan, Feri Yuni Asiyah; Hasibuan, Hanisah; Nasution, Lia Mardiana (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Unutilized corn cob waste damages the environment and reduces land sustainability. Processing it into organic fertilizer can support a circular economy and reducing waste. This study was aimed to analyze the attitudes, skills, and achievements of farmers' SDGs in processing corn cob waste into organic fertilizer. The method used was counseling and training for 30 farmers. The instrument used was a questionnaire to measure attitudes and skills, with 10 items each. The results showed that there was a significant increase in farmers' attitudes and skills, respectively, with an average score of 0.994 (very accepting category) and 0.993 (very skilled category). The findings concluded that counselling and training can improve positive attitudes and skills of farmers in processing corn cob into organic fertilizer. Thus, the objectives of the Sustainable Development Goals related to food security, environmental protection, independent and competitive farmer groups, local economic growth in Pakpak Bharat could be achieved.